Experimental evidence of resonant energy collisional transfers between argon 1s and 2p states and ground state H atoms by laser collisional induced fluorescence. (7th April 2015) - Carbone, Emile; van Dijk, Jan; Kroesen, Gerrit
Abstract: In this paper, laser collisional induced fluorescence (LCIF) is used to probe resonant excitation transfers in an argon/hydrogen plasma resulting from heavy particle collisions. Different radiative transitions between the 1s and 2p states (in Paschen's notation) of argon are optically pumped by a nanosecond laser pulse. The spontaneous fluorescence and collisional responses of the argon and hydrogen systems are monitored by optical emission spectroscopy. A surfatron plasma source is used to generate an argon plasma with a few per cent hydrogen addition at pressures between 0.65 and 20 mbar. The electron density is measured independently by means of Thomson scattering. The overall response of the plasma due to optical pumping of argon is briefly discussed and an overview of the known heteronuclear excitation transfers in an argon/hydrogen plasma is given. The propagation of the shortcut in the Ar(1s) to H( n = 2) excitation transfer due to the optical pumping of the Ar(1s) states is seen in the atomic hydrogen LCIF responses. For the first time, we give direct experimental evidence of the existence of an efficient excitation transfer: Additionally, measurements are performed in order to estimate the resonant energy transfer between the resonant argon 1s states and hydrogen atoms: for which no previously measured cross sections could be found in the literature. These are extra quenching channels of argon 1s and 2p states that should be included in collisional–radiative modeling of argon–hydrogen discharges. The high repetition rate of the dye laser allows us to obtain a high sensitivity in the measurements. LCIF is shown to be a powerful tool for unraveling electron and also heavy particle excitation channels in situ in the plasma phase. The technique was previously developed for measuring electron or species densities locally in the plasma, but we show that it can be advantageously used to probe collisional transfers between very short-lived species which exist simultaneously only in the plasma phase.